2021
DOI: 10.1016/j.kint.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The ROMANOV study found impaired humoral and cellular immune responses to SARS-CoV-2 mRNA vaccine in virus-unexposed patients receiving maintenance hemodialysis

Abstract: The ROMANOV study found impaired humoral and cellular immune responses to SARSCov-2 mRNA vaccine in virus unexposed patients receiving maintenance hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 20 publications
6
78
1
Order By: Relevance
“…The spike glycoprotein mediates virus entry into target cells via the ACE2 receptor and it has been shown that antibodies directed against the RBD can block viral infection of human cells in vitro and counter viral replication in vivo (26)(27)(28)(29)(30). In line with these studies, and despite the fact that the titers were lower than those observed in a cohort of 30 vaccinated healthy volunteers (31), sera of infected transplant recipients still very efficiently block pseudo-virus entry in human cells in vitro (Figure 3C). A positive correlation between anti-RBD IgG titer and the result of the in vitro neutralization assay was demonstrated (Figure 3D).…”
Section: Presence Of Neutralizing Igg Correlates With Protection Against Covid-19 In Transplant Recipientsmentioning
confidence: 74%
“…The spike glycoprotein mediates virus entry into target cells via the ACE2 receptor and it has been shown that antibodies directed against the RBD can block viral infection of human cells in vitro and counter viral replication in vivo (26)(27)(28)(29)(30). In line with these studies, and despite the fact that the titers were lower than those observed in a cohort of 30 vaccinated healthy volunteers (31), sera of infected transplant recipients still very efficiently block pseudo-virus entry in human cells in vitro (Figure 3C). A positive correlation between anti-RBD IgG titer and the result of the in vitro neutralization assay was demonstrated (Figure 3D).…”
Section: Presence Of Neutralizing Igg Correlates With Protection Against Covid-19 In Transplant Recipientsmentioning
confidence: 74%
“…Even though age might be a factor in the immune response it is hardly the sole explanation. In our patient cohort the mean age was 69.4 years, in the ROMANOV-study [ 9 ] 64.9, and in the three other studies, 67.6, 67.4, 71.2 and 68.6 years, respectively [ 10 – 13 ]. Perhaps differences in the assessment of the cellular response thus may the most important factor to consider and warrants further evaluate.…”
Section: Discussionmentioning
confidence: 91%
“…There are few studies that have addressed the cellular response to SARS-CoV-2 BNT162b2 mRNA vaccine in HD-patients [ 9 13 ]. In the ROMANOV study a decreased cellular response to the BNT162b2 vaccine was found [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their increased vulnerability to severe COVID-19, kidney transplant recipients need to be effectively vaccinated. Although kidney transplantation candidates receiving chronic haemodialysis also have a defective response to the COVID-19 mRNA vaccine 9 , this defect is milder than that observed in transplant recipients being treated with immunosuppressive drugs. COVID-19 vaccination should therefore be administered during the pre-transplant waiting period.…”
mentioning
confidence: 96%